Morphological identification of plant parasitic nematodes found in roots and soil of pomelo (Citrus maxima (J. Burm.) Merr.) - Almasco, A. Jr.; Yabut, A. J.; Zamora, M. J.; Alvarez, L. V.; Mapanao, C. P.; Rendon, A. O.; Zurbano, L. Y.; Bellere, A. D. (International Journal of Agricultural Technology, 2021)
Pomelo (Citrus maxima) is a tropical fruit plant originated from Southeast Asia. It is generally eaten and is known for its sour taste and richness in vitamin C and was traditionally used in medicine. Additionally, Pomelo is widely distributed throughout the country’s regions and is one of the predominant citruses planted. In the Philippines, the pomelo industry has created a higher market value and provides in the farming community. However, the growth in the said industry is threatened by different factors, and one of those is plant-parasitic nematodes. Thus, the study focused on identifying and determining the presence of parasitic plant nematode in C. maxima roots and soil within its rhizospheres. Morphological identification was done using a light microscope to classify the nematodes based on their physical characters like the stylet, knobs, tail, and buccal cavity, lip region, location of body regions, and the size and length of the body. Dichotomous keys, photographs from the database (NemaPlex), and related literature were used for genus-level identification while morphometrics was done to verify and identify the species of the plant-parasitic nematode. Based on morphological analysis of C. maxima, the identified free-living nematodes are Aphelenchusp. under Order Dorylaimida, Mononchus sp. under Order Mononchida, Rhabditis sp. under Order Rhabditida and a plant-parasitic type Tylenchulus spp. under Order Tylenchida with a relative frequency of 80%, 60%, 60%, and 100%, respectively. Moreover, Molecular identification is highly recommended to determine the species level of the collected nematode.